Efeito da taxa de aquecimento na obtenção do compósito CeO2-Mn3O4 como fotocatalisador na descoloração do corante C.I. reactive red 195 - Geron, Eduardo Luiz Bolson (2021)
In this work, the results of the characterization and application of the CeO2-Mn3O4 composite as photocatalyst for the decolorization of C.I. Red Dye 195, obtained by thermal decomposition of 8-Hydroxyquinolinates of Ce and Mn, are shown. This work can be divided into three steps. The first step is synthesizing metallic Ce and Mn chelates by chemical co-precipitation, starting from its nitrates and using 8-Hidroxyquinoline as a chelating agent, raising the solution’s pH to 9 with NH4OH and characterizing them by Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), Simultaneous Thermal Analysis (TGA/DTG/DTA) and Scanning Electron Microscopy (SEM). The second step is obtaining CeO2-Mn3O4 composite in a muffle, through the previously synthesized chelates thermal decomposition, at 600, 700 and 800 ºC, at heating rates of 05, 10 and 20 ºC min-1 and characterizing it by X-Ray Diffraction (XRD) with Rietveld Refinement and Scanning Electron Microscopy (SEM). The third step being the study of the discoloration of C.I. Reactive Red 195 dye using samples CM600/05, CM600/10, and CM600/20 as potential photocatalysts, and their characterization by Zero Charge Point (ZCP) and UV-VIS Region Diffuse Reflectance Spectroscopy (DRS). Based on the chelates characterizations, it was possible to observe the formation of different Ce and Mn chelates by the method employed, in the form of particle agglomerates, having different residual masses after heat treatment. The composites characterizations show us CeO2-Mn3O4 composite formation with CeO2 as major phase, regardless the final obtaining temperature or heating rate used, varying only its crystallinity and crystallite sizes, ranging between 6.8 and 20.1 nm for CeO2, and between 16.0 and 35.4 nm for Mn3O4; and, that its particles undergo a coalescence process at higher obtaining temperatures. Regarding to photocatalysts characterization, they have a ZCP value of 8.0, and band-gap values between 4.55 and 4.62 eV. Regarding the photocatalytic tests, it was shown a great adsorbent potential from the samples in the Adsorption Tests, ranging from 26 to 55% of the initial dye concentration, while it was shown a decrease in the removal effectiveness of dye color in the Photocatalysis Tests when compared to Photolysis Test, ranging between 80 and 90% for Photocatalysis, and 93% for Photolysis.